Extracts from Tribulus species may modulate platelet adhesion by interfering with arachidonic acid metabolism. (February 2015) - Olas, Beata; Hamed, Arafa I.; Oleszek, Wieslaw; Stochmal, Anna
Abstract The present work was designed to study the effects of crude extracts from Tribulus pterocarpus, T. pentandrus and T. parvispinus on selected biological functions of human blood platelets in vitro. Platelet suspensions were pre-incubated with extracts from aerial parts of T. pterocarpus, T. pentandrus and T. parvispinus, at the final concentrations of 0.5, 5 and 50 µg/ml. Then, for platelet activation thrombin, was used. The effects of crude extracts from T. pterocarpus, T. pentandrus and T. parvispinus on adhesion of blood platelets to collagen were determined by method according to Tuszynski and Murphy. Arachidonic acid metabolism was measured by the level of thiobarbituric acid reactive substances (TBARS). In these studies we also compared the action of tested crude plant extracts with the effects of the polyphenolic fraction isolated from aerial parts of T. pterocarpus, which has antiplatelet and antioxidative properties. The performed assays demonstrated that the tested crude extract from T. pterocarpus and the phenolic fraction from T. pterocarpus might influence the platelet functions in vitro. The inhibitory, concentration-dependent effects of this tested extract and its phenolic fraction on adhesion of resting platelets and thrombin – stimulated platelets to collagen was found. We also observed that the crude extract from T. pterocarpus, like the polyphenolic fraction from T. pterocarpus reduced TBARS production in blood platelets. In the comparative studies, the tested crude extract from T. pterocarpus was not found to be more effective antiplatelet factor, than the polyphenolic fraction from this plant. The results obtained suggest that T. pterocarpus may be a promising source of natural compounds, valuable in the prevention of the enhanced activity of blood platelets in numerous cardiovascular diseases.